SALIVARY PROFILE AND XEROSTOMIA ON THE ELDERLY IN DEPOK, WEST JAVA, INDONESIA: ANALYSIS OF DEMOGRAPHIC FACTORS AND SYSTEMIC DISEASE - N, Lutfi Laili; Rahmayanti, Febrina; Sarsito, Afi Savitri (International Journal of Applied Pharmaceutics, 2018)
Objective: The objective of this study is to determine the profiles of saliva between sexes, age groups, types of systemic disease, medications, and xerostomia on an elderly population in Depok. Methods: The study was observational analytical with a cross-sectional study design. Sampling was through a consecutive sampling technique in subjects aged â‰¥60 years living in Depok. Subjects were examined for their saliva's volume, stimulated and unstimulated salivary analysis, pH, and buffer capacity. Subjects answered fox questionnaires about xerostomia and questionnaires about systemic diseases and medications. Results: Gender had a significant difference in salivary flow rate but was not significant to pH or buffer capacity. There were no significant differences between types of salivary profile among age, systemic diseases, and medications. The correlation coefficient between xerostomia and stimulated flow rate was higher (0.426) than the unstimulated flow rate (0.303). Conclusion: The unstimulated and stimulated flow rates exhibited a significant difference between men and women but did not differ significantly between age groups, systemic diseases, or medications. The pH and buffer capacity was not significantly different between sexes, age groups, type of systemic diseases, or medications. Xerostomia was associated with salivary flow rate.